(untitled) (World Bulletin of Management and Law, 2022)
The terms of deadline used in civil-legal relations are appointed on the grounds established by civil legislation. Processual actions are carried out within the time limits established by law. In this article highlights of term deadline and issues of processual deadline in the national law in Uzbekistan